Determinación del rendimiento del grano, en la reintroducción de cuatro variedades de cebada (hordeum vulgare l.) mediante la aplicación de la abonadura orgánica en la zona Pimampiro Provincia de Imbabura” - Yar Narváez, Pedro Fernando (2013)
This work was conducted in the community of San Juan, Canton Pimampiro, Imbabura Province, in order to study the behavior of four varieties of barley (Bordean vulgare) based on organic Fertilisation. Established treatments are four varieties of barley: lNlAP-Guaranga 2010, shyris 43, 2003 Pacha, and lNlAP-Cañicapa. Applying a dose of 4000 kg / ha of compost. As guinea pigs rotted manure and vermicompost. The research design was applied Divided Plots (DPV) with four treatments (barley varieties Fertilisation and two organic products) and three replications or blocks. Plots treated with an area of 16 m², and the total area of 808 m² experiment. Variables were assessed: days after sowing germination was at 8 days, and the coefficient of variation was 7.80%, in this variable was reported that it presented the greatest value lNlAP varieties Shiri Guaranga 2010 and 43, with 6.67 days and the lowest value Pacha lNlAP 2003, with 6.44 days. In subtratamientos the highest value is obtained control without organic manuring, with 7.00 days, statistically equal to the application of manure guinea pigs at a dose of 4000 kg / ha, with 6.50 days and these statistically superior to other treatments, with the application of vermicompost at a dose of 4000 kg / ha which had the lowest value, with 6.25 days. Plant height (cm) at 40, 80 and 120 days (dds) plant diameter (cm) at 40, 80 and 120 days (dds). Days to tasseling (dds). Number of grains per spike. Days of harvest. Weight in kg dry grain produced. Performance kl per ha. Economic analysis, all variables applied were determined with analysis of variance, using the Tukey test at 5%.